Alternative music playlists on the radio: Flow experience and appraisal during the reception of music radio programs. (March 2017) - Ruth, Nicolas; Spangardt, Benedikt; Schramm, Holger
It is of fundamental importance for radio broadcasting companies that their listeners do not turn off the radio or switch to another station. Audiences continue listening if they like the program – especially the music. This positive appraisal can be explained by the concept of flow (Csikszentmihalyi, 1975), which illustrates how the right balance between the challenge of completing a task and the skill of the individual can lead to a particularly fulfilling mental state. We therefore conducted two 2 × 2 between-subjects experiments in cooperation with a major German broadcasting company in which we varied the complexity and familiarity of a 1-hour prime time radio program. In Study 1 we examined the effects of Adult Contemporary radio programs on a sample of the appropriate target group (120 participants, 51% female, 30 to 39 years old), while in Study 2, equivalent Contemporary Hit radio programs were evaluated by that genre's younger target group (217 participants, 49% female, 14 to 31 years old). We found that, dependent on the musical skill or listening modes of the recipients, the complexity of the music programs could be associated with higher or lower flow experiences, which in turn had an influence on positive listener appraisal.